An empirical study on the index system of rational drug use in children with primary nephrotic syndrome: A cross-sectional study. Issue 32 (7th August 2020) - Lin, Mao; Huang, Liang; Zeng, Linan; Zhang, Lingli
Abstract : Abstract: In the study's early stage, the research group had established an evaluation index system for the rational drug use of primary nephrotic syndrome in children. To assess the feasibility of the established index system, we conducted this empirical study. The cross-sectional study was conducted by using the Hospital Information System to extract some general clinical data of hospitalized children with primary nephrotic syndrome, which included registration number, age, sex, diagnosis and medication, etc. Utilize the SPSS23.0 software and Excel 2016 to descriptively analyze information. 224 hospitalized children with primary nephrotic syndrome who met the inclusion criteria were included, ranging from 18 years old and 10 months to 11 months and 23 days, with an average age of 8.40, plus or minus 4.30 years. 148 males (66.07%) and 76 females (33.93%). The duration of hospitalization was 1–57 days, with an average hospitalization time of 10.59 days. The most common is respiratory infections, such as the bronchopneumonia, the mycoplasma pneumonia, etc. This study had successfully completed the measurement of the evaluation index system for the rational drug use of primary nephrotic syndrome in children. All indicators are feasible, but the operability and applicability need further research and improvement.